Gut Microbiota Richness and Composition and Dietary Intake of Overweight Pregnant Women Are Related to Serum Zonulin Concentration, a Marker for Intestinal Permeability - Kati Mokkala; Henna Röytiö; Eveliina Munukka; Sami Pietilä; Ulla Ekblad; Tapani Rönnemaa; Erkki Eerola; Asta Laiho; Kirsi Laitinen (AMER SOC NUTRITION-ASN, 2022)
Background: Increased intestinal permeability may precede adverse metabolic conditions. The extent to which the composition of the gut microbiota and diet contribute to intestinal permeability during pregnancy is unknown.Objective: The aim was to investigate whether the gut microbiota and diet differ according to serum zonulin concentration, a marker of intestinal permeability, in overweight pregnant women.Methods: This cross-sectional study included 100 overweight women [mean age: 29 y; median body mass index (in kg/m(2)): 30] in early pregnancy (<17 wk of gestation; median: 13 wk). Serum zonulin (primary outcome) was determined by using ELISA, gut microbiota by 16S ribosomal RNA sequencing, and dietary intake of macro- and micronutrients from 3-d food diaries. The Mann-Whitney U test was used for pairwise comparisons and linear regression and Spearman's nonparametric correlations for relations between serum zonulin and other outcome variables.Results: Women were divided into "low" (<46.4 ng/mL) and "high" (>= 46.4 ng/mL) serum zonulin groups on the basis of the median concentration of zonulin (46.4 ng/mL). The richness of the gut microbiota (Chao 1, observed species and phylogenetic diversity) was higher in the low zonulin group than in the high zonulin group (P = 0.01). The abundances of Bacteroidaceae and Veillonellaceae, Bacteroides and Blautia, and Blautia sp. were lower and of Faecalibacterium and Faecalibacterium prausnitzii higher (P < 0.05) in the low zonulin group than in the high zonulin group. Dietary quantitative intakes of n-3 (omega-3) polyunsaturated fatty acids (PUFAs), fiber, and a range of vitamins and minerals were higher (P < 0.05) in women in the low zonulin group than those in the high zonulin group.Conclusions: The richness and composition of the gut microbiota and the intake of n-3 PUFAs, fiber, and a range of vitamins and minerals in overweight pregnant women are associated with serum zonulin concentration. Modification of the gut microbiota and diet may beneficially affect intestinal permeability, leading to improved metabolic health of both the mother and fetus. This trial was registered at clinicaltrials.gov as NCT01922791.